Incidence of Fibrocalculous Pancreatic Diabetes in Chattogram (Journal of Chittagong Medical College Teachers' Association, 2020)
Background : Fibrocalculous Pancreatic Diabetes (FCPD) is a unique form of diabetes secondary to chronic pancreatitis  usually found in tropical countries of the world. Fibrocalculous pancreatic diabetes affects young individuals and runs an aggressive course to reach the endpoints of diabetes, pancreatic calculi and exocrine pancreatic dysfunction (Steatorrhoea) in the majority of cases. There are characteristic features of FCPD clinically, radiologically, ultrasonographically which distinguish it from diabetes of other causes and also from chronic pancreatitis of other aetiologies seen in temperate zones, e.g. alcoholic chronic pancreatitis. To observed the incidence of FCPD among the patients attending at the hospital.  Materials and methods: We conducted this study among 487 patients over a period of January 2016 to December 2017 in different wards of Chittagong Medical College Hospital which is the largest hospital in Chattogram, Bangladesh. FCPD was diagnosed based on the standard criteria.Results: The incidence of fibrocalculous pancreatic diabetes is 0.61% among the diabetic patients in Chattogram. Mean age of the patients is 39.7 ± 10 years. Mean age of onset of diabetes is 37.3±15 years.  Conclusion: This study reports the incidence of fibrocalculous pancreatic diabetes in Chattogram district, the second largest city in Bangladesh.JCMCTA 2020 ; 31 (2) : 140-144